ANALYSIS OF STUDENTS' LEARNING DIFFICULTIES ON PROTISTA MATERIAL CLASS X MIA PANCASILA EDUCATION FOUNDATION SAWIT SEBRANG 2024/2025 - Sari, Widya; Rangkuti, Marlinda Nilan Sari (Jurnal Pelita Pendidikan, 2025)
This study aims to determine students' learning difficulties in the material protista based on learning outcome indicators and cognitive aspects and factors causing learning difficulties of class X students of SMA Yayasan Pendidikan Pancasila in the 2024/2025 Academic Year. This type of research is descriptive-quantitative research using several data collection techniques, namely questionnaires and learning outcome tests. The most dominant external factor causing students' difficulties in learning biology protista material in class X MIA Yayasan Pendidikan Pancasila is the Family Environment factor in the Very High Difficulty category with an overall average of 91.96%. Meanwhile, the most dominant internal factor causing students' difficulties in learning biology protista material in class X MIA Swab Yayasan Pendidikan Pancasila is the Intelligence factor in the Very High Difficulty category with an overall average of 92.53%.